Qualitative Research in Psychology - Hanurawan, Fattah (Journal of Educational, Health and Community Psychology, 2012)
Â AbstractQualitative research is a research methodÂ  studying subjective meaning of participantâs world aboutÂ  an object researched. Steps of qualitative research in psychology are: researchers select research topic, researchers formulate research questions, researchers design the study, researchers collect data, researchersanalyses data, researchers generate findings, researchers validate findings, and researchers write research report. Some of the qualitative research designs are grounded research, phenomenology research, case study research, and ethnography research. In some situations, researchers often meet questions that reach beyond the prescription of the APA ethical guidelines concerning human participants. Researchers of qualitative research in psychology can generalize their research findings to other people, times, or treatments to the degree to which they are similar to other people, times, or treatments in the original research (naturalistic generalization). There are some strategies for expanding qualitative research as a research approach so the methodology can be accepted as one significant method in understanding psychological phenomena.Keywords:qualitative research, psychology.